Three-Dimensional Cavitation Bubble Simulations Based on Lattice Boltzmann Model Coupled with Carnahan-Starling Equation of State (Communications in Computational Physics, 2018)
The Shan-Chen multiphase lattice Boltzmann model (LBM) coupled withCarnahan-Starling real-gas equation of state (C-S EOS) was proposed to simulate three-dimensional(3D) cavitation bubbles. Firstly, phase separation processes were predictedand the inter-phase large density ratio over 2×104 was captured successfully.The liquid-vapor density ratio at lower temperature is larger. Secondly, bubble surfacetensions were computed and decreased with temperature increasing. Thirdly, theevolution of creation and condensation of cavitation bubbles were obtained. The effectivenessand reliability of present method were verified by energy barrier theory.The influences of temperature, pressure difference and critical bubble radius on cavitationbubbles were analyzed systematically. Only when the bubble radius is largerthan the critical value will the cavitation occur, otherwise, cavitation bubbles will dissipatedue to condensation. According to the analyses of radius change against timeand the variation ratio of bubble radius, critical radius is larger under lower temperatureand smaller pressure difference condition, thus bigger seed bubbles are needed toinvoke cavitation. Under higher temperature and larger pressure difference, smallerseed bubbles can invoke cavitation and the expanding velocity of cavitation bubblesare faster. The cavitation bubble evolution including formation, developing and collapsewas captured successfully under various pressure conditions.